Nilai Estetis Pada Kemasan Makanan Tradisional Yogyakarta - Setiawan Sabana (ITB Journal Publisher, LPPM ITB, 2007)
This research is focused on investigating the aesthetical and philosophical values of traditional food packaging in Yogyakarta, whereas much of traditional values are still applied and existed in the daily life. It is thought that the philosophical value of traditional food packaging is related to its use in the traditional ceremonies of the Yogyakarta Palace, such as Garebeg Mulud (Sekaten), Garebeg Syawal, Garebeg Idhul Adha, Tumplak Wajik, and Labuhan. Although some of traditional food packaging are also used in the people's ceremony, such as birth, wedding, and funeral ceremonies. Accordingly, traditional food packagings are mostly used to represent symbols that link to the life of the people of Yogyakarta. The aesthetical value of traditional food packaging can be identified from its visual elements, such as shapes, lines, textures, colors, masses (volumes), spaces, and the composition of those elements using natural materials such banana leaf and young coconut leaf. The intertwined of each element carry on meanings and therefore when modern materials (papers and plastics) are applied, most of traditional food packaging degrades their actual and symbolical meanings.